Ukraine - Ukrzaliznytsia Modernization Strategy : Summary Report - Using Market Opening to Catalyze Railway Reforms - World Bank Group (World Bank, Washington, DC, 2019)
This summary report assembles and distills the main finding and recommendations of five separate policy notes that originated in a request from Ukraine’s Ministry of Infrastructure (MoI) and state-owned railway company, JSC Ukrzaliznytsia (UZ) to the World Bank to help address specific topics concerning Ukraine’s railway sector. The topics were: (1) railway market opening for cargo services; (2) loss-making long-distance passenger services; (3) selected Cargo business issues; (4) debt management; and (5) infrastructure asset management and prioritization of investment. Asset management strategy and life-cycle costing in the renewal and reconstruction of UZ’s railway infrastructure network. This summary note is organized with the market opening as the anchor for catalyzing and achieving the modernization of UZ and putting it in a strong position to compete with other railways once the market is opened. And while many of the regulatory and institutional actions will depend on the pending railway law, UZ and MoI can continue and in some cases start preparations to be ready once the law is passed.